The association of early post-resuscitation hypotension with discharge survival following targeted temperature management for pediatric in-hospital cardiac arrest. (August 2019) - Topjian, Alexis A.; Telford, Russell; Holubkov, Richard; Nadkarni, Vinay M.; Berg, Robert A.; Dean, J. Michael; Moler, Frank W.; ,; Moler, Frank W.; Meert, Kathleen L.; Hutchinson, Jamie S.; Newth, Christopher J.L.; et al.
Abstract: Aim: Approximately 40% of children who have an in-hospital cardiac arrest (IHCA) in the US survive to discharge. We aimed to evaluate the impact of post-cardiac arrest hypotension during targeted temperature management following IHCA on survival to discharge. Methods: This is a secondary analysis of the therapeutic hypothermia after pediatric cardiac arrest in-hospital (THAPCA-IH) trial. "Early hypotension" was defined as a systolic blood pressure less than the fifth percentile for age and sex for patients not treated with extracorporeal membrane oxygenation (ECMO) or a mean arterial pressure less than fifth percentile for age and sex for patients treated with ECMO during the first 6 h of temperature intervention. The primary outcome was survival to hospital discharge. Results: Of 299 children, 142 (47%) patients did not receive ECMO and 157 (53%) received ECMO. Forty-two of 142 (29.6%) non-ECMO patients had systolic hypotension. Twenty-three of 157 (14.7%) ECMO patients had mean arterial hypotension. After controlling for confounders of interest, non-ECMO patients who had early systolic hypotension were less likely to survive to hospital discharge (40.5% vs. 72%; adjusted OR [aOR] 0.34; 95%CI, 0.12–0.93). There was no difference in survival to discharge by blood pressure groups for children treated with ECMO (30.4% vs. 49.3%; aOR = 0.60; 95%CI, 0.22–1.63). Conclusions: In this secondary analysis of the THAPCA-IH trial, in patients not treated with ECMO, systolic hypotension within 6 h of temperature intervention was associated with lower odds of discharge survival. Blood pressure groups in patients treated with ECMO were not associated with survival to discharge.